Silver resistance in Gram-negative bacteria: a dissection of endogenous and exogenous mechanisms. (6th January 2015) - Randall, Christopher P.; Gupta, Arya; Jackson, Nicole; Busse, David; O'Neill, Alex J.
Abstract: Objectives: To gain a more detailed understanding of endogenous (mutational) and exogenous (horizontally acquired) resistance to silver in Gram-negative pathogens, with an emphasis on clarifying the genetic bases for resistance. Methods: A suite of microbiological and molecular genetic techniques was employed to select and characterize endogenous and exogenous silver resistance in several Gram-negative species. Results: In Escherichia coli, endogenous resistance arose after 6 days of exposure to silver, a consequence of two point mutations that were both necessary and sufficient for the phenotype. These mutations, in ompR and cusS, respectively conferred loss of the OmpC/F porins and derepression of the CusCFBA efflux transporter, both phenotypic changes previously linked to reduced intracellular accumulation of silver. Exogenous resistance involved derepression of the SilCFBA efflux transporter as a consequence of mutation in silS, but was additionally contingent on expression of the periplasmic silver-sequestration protein SilE. Silver resistance could be selected at high frequency (>10 −9 ) from Enterobacteriaceae lacking OmpC/F porins or harbouring the sil operon and both endogenous and exogenous resistance were associated with modest fitness costs in vitro . Conclusions: Both endogenous and exogenous silver resistance are dependent on the derepressed expression of closely related efflux transporters and are therefore mechanistically similar phenotypes. The ease with which silver resistance can become selected in some bacterial pathogens in vitro suggests that there would be benefit in improved surveillance for silver-resistant isolates in the clinic, along with greater control over use of silver-containing products, in order to best preserve the clinical utility of silver.